Epidemiological investigation of Paramphistomiasis in cattle at selected areas of Sirajgonj district of Bangladesh (Journal of the Bangladesh Agricultural University, 2012)
To investigate the Epidemiology of Paramphistomum infection in cattle, faecal samples from 360 cattle were collected from individual areas of the Sirajgonj district from March 2009 to April 2010. One hundred and ninety one animals (53.1%) were infected with single or multiple species of Paramphistomum. Age of animals significantly (P